Interpretasi Makna Frasa “Sisa Israel” Menurut Roma 11:5-10 - Sanda, Hendrik Yufengkri; Kudati, Elsa Ayudia (JURNAL LUXNOS, 2025)
The phrase "Remnant of Israel" in Romans 11:5-10 is a theological concept that is often debated in New Testament studies. Some interpreters understand this phrase to refer to the ethnic remnant of Israel who remain faithful to God, while others interpret it as believers from various nations who are chosen by God through grace. This article aims to interpret the meaning of the phrase "Remnant of Israel" in the context of Romans 11:5-10 using an exegetical approach and biblical textual analysis. The results of the study show that the phrase "Remnant of Israel" in Romans 11:5-10 has two dimensions of meaning. First, it refers to the Jews who remain faithful to God, as happened in the time of Elijah when God preserved 7,000 people who did not worship Baal. Second, Paul expands this concept by linking it to God's grace, which allows not only the ethnic remnant of Israel, but also believers from other nations to become part of God's chosen people. Thus, the "Remnant of Israel" is not only limited to physical Israel, but also includes spiritual Israel, namely the church that believes in Jesus Christ as the Messiah. Study affirms that God's election is not based on human effort or goodness, but solely by His grace. This understanding has theological relevance for believers today, especially in understanding the relationship between Israel and the church in God's plan of salvation.